Dropshipper Hijab Haven: A Solution for Stylish and Comfortable Hijabs - Nurul Fahmi; Anisa, Nor (LPPM Universitas Sari Mulia, 2024)
Hijab Haven is an innovative startup that aims to provide hijab collections with fashionable, comfortable, and functional designs to fulfill the needs of modern Muslim women. Through a technology-based approach and digital marketing, the startup offers solutions that not only improve customer experience but also support more efficient business management. This research uses a descriptive method with a qualitative approach to evaluate digital marketing strategies, optimization of stock management, and user-friendly e-commerce interface design. Results show that the combination of social media strategy, use of cloud-based technology, and business management training significantly improved Hijab Haven's competitiveness as well as sustainability in the Muslim fashion market. The findings provide important insights into how MSMEs can leverage technology to achieve sustainable growth in the digital age. This research recommends further development in product innovation and the use of artificial intelligence for market trend analysis to improve service personalization.